USE OF 125IODINE SEEDS (ROLLIS) FOR INTRA-OPERATIVE LOCALIZATION OF NONPALPABLE BREAST LESIONS: ANALYSIS OF THE IMPLANT OF 338 SEEDS IN 284 PATIENTS - Penna, Antonio Campbell; Franca, Carlos Antonio da Silva; Oliveira, Maria Veronica Fonseca Torres de; Fonseca, Lea Mirian Barbosa da; Saldanha, Paula de Azevedo Brant; Costa, Mauricio Magalhães; Balen, Jacir; Rocha, Augusto Cesar Peixoto; Pereira, Fernanda Philadelpho Arantes; Andrade, Valesca Caldoncelli; et al. (Mastology, 2017)
Objective: To analyze the feasibility, efficacy and results of the use of 125Iodine seeds for intra-operative localization of nonpalpable breast lesions. Method: Retrospective review of 284 patients, referred by various breast specialist surgeons, with radiologically detected but clinically nonpalpable microcalcifications or nodules, submitted to pre-operatory 125Iodine seed implant, between July 2012 and September 2016. A total of 338 seeds were implanted in ordinary radiologic departments, supported by ultrasonography or mammography exams, chosen according to the morphologic aspect of the lesion. Radioguided surgical procedure took place on the same day or few days after the implant of the seeds, with the help of a radiation detector called Gamaprobe, which directs the surgeons towards the radioactive seeds and to the lesion to be resected. Results: All implants were performed as outpatient procedures, with patients immediately returning to their daily activities. No complications such as pain, bleeding, infeccion and haematoma were recorded. Pathologists had no difficulty in preparing the surgical specimens for histopathologic analysis. Surgical safety margins were considered adequate in all pathologic reports, with no need for re-operations. The healing process was not jeopardized by radiation, and the surgeons were pleased with the improvement on intraoperative lesions localizations and shortening on operatory time. Cosmetic results were well accepted by the patients. Conclusion: The 125Iodine seed implant is an effective alternative method for intraoperative localization of radiologically detectable and clinically nonpalpable breast lesions.